2014
DOI: 10.1007/s11274-014-1773-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic growth of microalgae: metabolic aspects

Abstract: Microalgae are considered photoautotrophic organisms, however several species have been found living in environments where autotrophic metabolism is not viable. Heterotrophic cultivation, i.e. cell growth and propagation with the use of an external carbon source under dark conditions, can be used to study the metabolic aspects of microalgae that are not strictly related to photoautotrophic growth and to obtain high value products. This manuscript reviews studies related to the metabolic aspects of heterotrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(71 citation statements)
references
References 84 publications
1
67
0
3
Order By: Relevance
“…Harsall reported that d ‐xylose was not utilized by microalgae for chemosynthesis, rather it acted as an inhibitor for the photosynthetic process. In another study, Neochloris oleabundans displayed a high growth rate when cultivated in 10 g/L of glucose but showed no growth when xylose and arabinose were used as a carbon sources …”
Section: Resultsmentioning
confidence: 99%
“…Harsall reported that d ‐xylose was not utilized by microalgae for chemosynthesis, rather it acted as an inhibitor for the photosynthetic process. In another study, Neochloris oleabundans displayed a high growth rate when cultivated in 10 g/L of glucose but showed no growth when xylose and arabinose were used as a carbon sources …”
Section: Resultsmentioning
confidence: 99%
“…Many photosynthetic organisms can also grow heterotrophically or mixotrophically using externally supplied organic carbon or with a combination of photosynthesis and imported organic carbon (Pringsheim and Wiessner, 1960;Koch, 2004;Harris, 2009a;Morales-Sánchez et al, 2015). The means by which photosynthetic cells coordinate these two modes of carbon metabolism are relatively unexplored (Sheen, 1994;Coruzzi and Bush, 2001;Halford and Paul, 2003;Smith and Stitt, 2007), but the elucidation of intracellular carbon regulatory networks has the potential to improve our understanding of photosynthetic cell growth and provide insights that will allow harnessing of photosynthesis for improved yields and storage of fixed carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Many specieso fa lgae are forced to metabolize through this metabolic pathway because they live in extreme environments that are deprived of solar radiation, so (photo)autotrophic metabolism is not possible. [37] Many studies have found that algaes pecies are capable of (chemo)heterotrophically metabolizing aw ide range of organic carbon sourcedu nder light-deprived environments. [37] Suitable microalgae for heterotrophic cultivation should have 1) the potential to metabolize and growi nl ight-deprived conditions;2 )the potentialf or rapid growth in sterilized culture media;a nd 3) the potential to metabolize aw ide range of organic carbon sources,s uch as acetate, pyruvate, lactate, saturated fatty acids,e thanol, glycolate,C 6s ugars, glycerol, disaccharides, C5 monosaccharides, and amino acids.…”
Section: Heterotrophic Metabolismmentioning
confidence: 99%